(untitled) (Colombia Medica, 2007)
Recently, Alphavirus have been used as expression vectors, among these, Semliki Forest virus (SFV), an enveloped virus, besides replicating itself in the cytoplasm, has the property to express structural proteins separately from nonstructural proteins, allowing a greater expression control. Vectors derived from SFV can have a broad range of applications. High viral titers can be obtained to efficiently express proteins in different cell lines. They can infect a wide spectrum of mammalian cells, as well as tissues. They are promising to be used on gene therapy as vehicles for specific gene delivery in vivo or in vitro, as much as in therapy against cancer as neuronal therapy, especially when a short term expression is necessary. Another studied aspect is SFV vectors applications in prophylactic or therapeutic vaccine production; the generation of important immune responses against different viral and tumor diseases is still been discussed. Development of new non-cytopathic vectors, temperature-regulated vectors, as well as others with persistent replication, will allow prolongation of expression. Due to these new advantages and to others already known, uses for vectors derived from SFV could be extended gradually, as long as undesired effects are controlled.